Perancangan Dan Implementasi Sistem Ekspor Impor Pada PT. Dawee Electronic Indonesia - Muhamad Fatchan (Jurnal SIGMA, 2021)
Dawee Electronic Indonesia is a company engaged in electronics producing PCB, where the system of import export data processing is still using Ms. Excell that there are some deficiencies such as penginputan data for the preparation of documents and reports, still use the book to sort the registration number. Therefore it is needed a new system that has been computerized to overcome the existing problems. This new system uses only analytical methods. By using Ms. Access and VB.Net program, this new system can solve the problems that occur at PT. Dawee Electronic Indonesia, which is the registration number on auto number, data input for document making and report is done once and BC documents 2.7, BC 4.0 and monthly report as its output which can be printed directly. The system used in PT. Dawee Electronic Indonesia needs to be improved because it affects the efficient time and quality of employees, because it uses a less good system. The author suggests for the manufacture of import export system which can produce an accurate and effective data report and there is also maintenance of the system. Keywords: Import Export System